Transcriptomic profiling of bovine blood dendritic cells and monocytes following TLR stimulation. Issue 11 (28th July 2020) - Barut, G. Tuba; Lischer, Heidi E. L.; Bruggmann, Rémy; Summerfield, Artur; Talker, Stephanie C.
Abstract: Dendritic cells (DC) and monocytes are vital for the initiation of innate and adaptive immune responses. Recently, we identified bona fide DC subsets in blood of cattle, revealing subset‐ and species‐specific transcription of toll‐like receptors (TLR). In the present study, we analyzed phenotypic and transcriptional responses of bovine DC subsets and monocytes to in vitro stimulation with four to six different TLR ligands. Bovine DC subsets, especially plasmacytoid DC (pDC), showed a clear increase of CCR7, CD25, CD40, CD80, CD86, and MHC‐II expression both on mRNA and protein level. Flow cytometric detection of p38 MAPK phosphorylation 15 min after stimulation confirmed activation of DC subsets and monocytes in accordance with TLR gene expression. Whole‐transcriptome sequencing of sorted and TLR‐stimulated subsets revealed potential ligand‐ and subset‐specific regulation of genes associated with inflammation, T‐cell co‐stimulation, migration, metabolic reprogramming, and antiviral activity. Gardiquimod was found to evoke strong responses both in DC subsets and monocytes, while Poly(I:C) and CpG preferentially triggered responses in cDC1 and pDC, respectively. This in‐depth analysis of ligand responsiveness is essential for the rational design of vaccine adjuvants in cattle, and provides a solid basis for comparative studies on DC and monocyte biology across species. Abstract : Transcriptomic responses of bovine blood dendritic cells and monocytes to innate stimulation revealed potential ligand‐ and subset‐specific regulation of genes associated with inflammation, antigen presentation, metabolism, and antiviral activity. These insights will promote the design of efficacious immunotherapeutics for cattle, and are a precious resource for comparative immunology.